Cardioprotective activity of fruit of Garcinia pedunculata on isoprenaline-induced myocardial infarction in rat - Ravi Mundugaru; Padmaja Udaykumar; Sivanesan Senthilkumar; Sudhakara Bhat (Bangladesh Pharmacological Society, 2016)
The present study reveals the protective effect of Garcinia pedunculata aqueous fruit extract in isoprenaline-induced myocardial infarction in Wistar rats. Isoprenaline (200 mg/kg) administration subcutaneous once daily for two consecutive days significantly (p<0.01) increased the CK-MB, AST, ALT, ALP activity and CRP (p<0.05) levels. Pretreatment with extract (400 mg/kg) orally for 14 consecutive days significantly ameliorated the effect of isoprenaline by reducing the activity of CK-MB and the levels of ALP, SGPT respectively. No significant changes were seen in the case of SGOT activity and CRP levels. Severe necrotic lesions in the myocardial tissue were observed in isoprenaline-treated group. In extract-treated group, mild degenerative changes of myo-cardial tissues to nearly normal cytoarchitecture were seen. The results indicate the cardioprotective effect of G. pedunculata against isoprenaline- induced myocardial infarction rat model.